Desain Aplikasi Biaya Sebagai Penetapan Tarif Praktek Bidan Swasta - Surtikanti, Surtikanti; Dewi Anggadini, Sri; Rachmanto, Adi (TERANG, 2024)
As long as this fee has not been calculated on a unit cost basis, the rates for midwives differ from one to another, even though they are in the same area. Tariff calculation is only based on the price of goods prevailing in the market. As a result of these differences in rates, people tend to choose private practicing midwives who provide lower rates for the same type of service. The practice of private midwives has not yet calculated the unit cost as the basis for setting tariffs. The purpose is to find out whether the rates currently used are appropriate or not with the unit cost. The data collection technique uses case studies because it only involves one partner unit, namely the midwife. The data collected was then analyzed through descriptive qualitative, namely explaining and explaining the conditions of partners in implementing the excel application regarding practice rates. The location of the community service partner at Midwife Anggraeni Linda Silfyani A.Md.Keb at Babakan Ciparay Bandung. After attending this training, private practice midwives were able to formulate a tariff pattern based on the unit cost that would be used at their practice site. From the explanation above, this dedication to the community is entitled Design Cost Application as the Basis for Determining Tariffs for Private Midwife Practice. From the community service that is carried out, it is hoped that it can minimize problems from partners and become a pilot project for other midwives who have the same problems.